Associations of airway inflammation and responsiveness markers in non asthmatic subjects at start of apprenticeship - Demange, Valérie (BioMed Central, 2010)
BACKGROUND: Bronchial Hyperresponsiveness (BHR) is considered a hallmark of asthma. Other methods are helpful in epidemiological respiratory health studies including Fractional Exhaled Nitric Oxide (FENO) and Eosinophils Percentage (EP) in nasal lavage fluid measuring markers for airway inflammation along with the Forced Oscillatory Technique measuring Airway resistance (AR). Can their outcomes discriminate profiles of respiratory health in healthy subjects starting apprenticeship in occupations with a risk of asthma? METHODS: Rhinoconjunctivitis, asthma-like symptoms, FEV1 and AR post-Methacholine Bronchial Challenge (MBC) test results, FENO measurements and EP were all investigated in apprentice bakers, pastry-makers and hairdressers not suffering from asthma. Multiple Correspondence Analysis (MCA) was simultaneously conducted in relation to these groups and this generated a synthetic partition (EI). Associations between groups of subjects based on BHR and EI respectively, as well as risk factors, symptoms and investigations were also assessed. RESULTS: Among the 441 apprentice subjects, 45 (10%) declared rhinoconjunctivitis-like symptoms, 18 (4%) declared asthma-like symptoms and 26 (6%) suffered from BHR. The mean increase in AR post-MBC test was 21% (sd = 20.8%). The median of FENO values was 12.6 ppb (2.6-132 range). Twenty-six subjects (6.7%) had EP exceeding 14%. BHR was associated with atopy (p < 0.01) and highest FENO values (p = 0.09). EI identified 39 subjects with eosinophilic inflammation (highest values of FENO and eosinophils), which was associated with BHR and atopy. CONCLUSIONS: Are any of the identified markers predictive of increased inflammatory responsiveness or of development of symptoms caused by occupational exposures? Analysis of population follow-up will attempt to answer this question.